Penerapan AQL (Acceptable Quality Level) Pada Proses Trimming Baju Tidur Untuk Perbaikan Mutu Di CV. Aliya - Kurniadi, Deri; Syahputra, Asep (Riset Sinergi Indonesia, 2023)
CV Aliya is an industrial business engaged in the garment sector in producing nightgowns. In producing nightgowns, CV Aliya has several factors that support production activities. The several supporting factors for these activities are raw materials, production processes and completion of the final production. From the results of the first observations and short interviews with business owner CV Aliya, CV Aliya produced orders for 6,000 nightgowns. The target to be achieved is 1,000 pieces/day. With the number of sewing operators as many as 31 people in the operator section. CV Aliya received complaints from buyers regarding the poor quality of the nightgowns produced by CV Aliya. There are types of complaints that occur, namely the presence of excess long threads on the inside of the clothes, both the result of leftover stitching threads that have not been trimmed, or from the material itself, resulting in uncomfortable nightgowns when worn by consumers. This study aims to apply AQL (Acceptabel Quality Level) at CV Aliya for quality improvement. The results of this study are from the results of applying the AQL (Acceptable Quality Level) in this study we get 12 rejects and not more than 14 which has been set in the AQL (Acceptable Quality Level) table, so these rejects or lots are accepted so that in applying the AQL (Acceptable Quality Level) method Quality Level) at CV Aliya is feasible to apply and compared to CV Aliya before applying the AQL (Acceptable Quality Level) and before applying the AQL (Acceptable Quality Level) method. Before applying the AQL (Acceptable Quality Level) method, CV Aliya received 30 pcs of rejects, while after using the AQL method, CV Aliya received a smaller reject, which was 12 and did not exceed the value provisions standardized by AQL